Guía estratégica para motivar el teletrabajo mediante el fomento de las habilidades blandas fundamentales en los trabajadores administrativos de empresas constructoras de mediana envergadura (2023)
This degree work structures a strategic guide to human talent focused on developing fundamental soft skills in workers in the administrative area of ​​a medium-sized construction company in order to motivate teleworking. The above is achieved through the construction of tactics and tools that support work practices in medium-sized construction companies, an analysis of the most relevant soft skills is carried out according to various authors through a bibliographic review, and subsequently the soft skills are consolidated. fundamental requirements that administrative workers require through testing of the real environment in a survey.